Inner Conflict of the Main Character of the Novel Saturday with Father by Adhitya Mulya: Literary Psychology and its Relevance to Literature Learning in High School - Nugroho, Rifky Dhimas; Maruf, Ali Imron Al (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This research aims to discuss the inner conflict of the main character of the novel Saturday Together with Father by Adhitya Mulya. Inner conflict that is relevant to literary learning. Methodology: This research is a note-taking technique carried out by recording documents or archives by reading intensively the novel Saturday with Father and taking active notes. The data analysis technique in this research is a semiotic technique, the way readers interpret literary texts referentially through linguistic signs. Results: The results of this research include: Id, Ego and Superego. Applications/Originality/Value: The relevance of the novel Saturday Together with Mr. Adhitya Mulya's work when used in high school learning, especially class.